2009
DOI: 10.1097/qai.0b013e3181a24b38
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sexual Abuse Is Highly Associated With HIV Risk-Taking Behavior and Infection Among MSM in the EXPLORE Study

Abstract: Background Previous studies have found high rates of childhood sexual abuse (CSA) among US men who have sex with men (MSM). CSA history has been associated with a variety of negative effects later in life including behaviors that place MSM at greater risk for HIV acquisition and transmission. The present analysis is the first to examine the longitudinal association between CSA and HIV infection, unprotected anal sex, and serodiscordant unprotected anal sex, as well as mediators of these relationships among a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
228
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 231 publications
(253 citation statements)
references
References 35 publications
17
228
1
7
Order By: Relevance
“…Individuals' engagement in risky sexual behaviours or UAI has been incriminated as the main contributor to the spread of the epidemic among them (Mumtaz, Hilmi, McFarland, Kaplan, & Akala, 2011;Mustanski, Newcomb, Du-Bois, Garcia, & Grov, 2011). Consistent with the results of several previous studies (El-Sayed, IA, & El-Gueniedy, 2008;Mimiaga et al, 2009;Morineau, et al, 2011;Poon, et al, 2013), the current study confirms that having multiple casual sex partners was one of the behavioural determinants strongly associated with HIV-risk sexual practice among the participants. Likewise, enjoyment associated with group sex practices and their preference to experience sexual sensation without condoms, coupled with the unavailability of condoms at time when such practices happened, were enablers to MSM engagement in UAI.…”
Section: Discussionsupporting
confidence: 81%
“…Individuals' engagement in risky sexual behaviours or UAI has been incriminated as the main contributor to the spread of the epidemic among them (Mumtaz, Hilmi, McFarland, Kaplan, & Akala, 2011;Mustanski, Newcomb, Du-Bois, Garcia, & Grov, 2011). Consistent with the results of several previous studies (El-Sayed, IA, & El-Gueniedy, 2008;Mimiaga et al, 2009;Morineau, et al, 2011;Poon, et al, 2013), the current study confirms that having multiple casual sex partners was one of the behavioural determinants strongly associated with HIV-risk sexual practice among the participants. Likewise, enjoyment associated with group sex practices and their preference to experience sexual sensation without condoms, coupled with the unavailability of condoms at time when such practices happened, were enablers to MSM engagement in UAI.…”
Section: Discussionsupporting
confidence: 81%
“…The higher tendency of sexual minority adolescents being sexually coerced raises concern over the higher risks for HIV and other STDs, as condoms are reportedly used less than half the time when sexual coercion occurs (Guadamuz et al, 2011;Manopaiboon et al, 2003). In addition, as many studies have shown, sexual coercion during adolescence is significantly associated with subsequent HIV risk-taking behaviors (Bensley, Van Eenwyk & Simmons, 2000;Brennan, Hellerstedt, Ross & Welles, 2007;Holmes & Slap, 1998;Mimiaga et al, 2009;O'Leary, Purcell, Remien & Gomez, 2003;Senn, Carey, Vanable, Coury-Doniger & Urban, 2006) According to Meyer (2003), such experiences of victimization and sexual coercion are distal minority stressors which can negatively impact mental well-being. In this study, we found a significant association between victimizations/sexual coercion and adverse mental well-being measures.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, MSM, particularly those who test often, may be aware of their risk but are unable to change their behavior for multiple syndemic psychosocial reasons, 57 including substance use difficulties, 32 mental health problems, 58 and the psychological sequelae of childhood sexual abuse, 59 and may thus utilize more frequent testing as a means of selfmonitoring. Depression was a significant burden for a large subset of this sample of MSM.…”
Section: Discussionmentioning
confidence: 99%